Regulation of the SOS response in Bacillus subtilis: evidence for a LexA repressor homolog. - Wojciechowski, M F (1991)
The inducible SOS response for DNA repair and mutagenesis in the bacterium Bacillus subtilis resembles the extensively characterized SOS system of Escherichia coli. In this report, we demonstrate that the cellular repressor of the E. coli SOS system, the LexA protein, is specifically cleaved in B. subtilis following exposure of the cells to DNA-damaging treatments that induce the SOS response. The in vivo cleavage of LexA is dependent upon the functions of the E. coli RecA protein homolog in B. subtilis (B. subtilis RecA) and results in the same two cleavage fragments as produced in E. coli cells following the induction of the SOS response. We also show that a mutant form of the E. coli RecA protein (RecA430) can partially substitute for the nonfunctional cellular RecA protein in the B. subtilis recA4 mutant, in a manner consistent with its known activities and deficiencies in E. coli. RecA430 protein, which has impaired repressor cleaving (LexA, UmuD, and bacteriophage lambda cI) functions in E.coli, partially restores genetic exchange to B. subtilis recA4 strains but, unlike wild-type E. coli RecA protein, is not capable of inducing SOS functions (expression of DNA damage-inducible [din::Tn917-lacZ] operons or RecA synthesis) in B. subtilis in response to DNA-damaging agents or those functions that normally accompany the development of physiological competence. Our results provide support for the existence of a cellular repressor in B. subtilis that is functionally homologous to the E. coli LexA repressor and suggest that the mechanism by which B. subtilis RecA protein (like RecA of E. coli) becomes activated to promote the induction of the SOS response is also conserved.